The Need for Antiepileptic Drug Chronotherapy to Treat Selected Childhood Epilepsy Syndromes and Avert the Harmful Consequences of Drug Resistance. (4th February 2017) - Manganaro, Sheryl; Loddenkemper, Tobias; Rotenberg, Alexander
Antiepileptic drug (AED) chronotherapy involves the delivery of a greater AED dose at the time of greatest seizure susceptibility usually associated with predictable seizure peaks. Although research has proven AED chronotherapy, commonly known as differential dosing, to be safe, well tolerated, and highly effective in managing cyclic seizure patterns in selected childhood epilepsies, conventional, equally divided AED dosing remains the standard of care. Differential dosing is more often applied in the emergency management of acute seizure clustering resulting from drug resistance—a harmful epilepsy-related consequence that affects 30% of children. Moreover, drug resistance is a major risk factor in status epilepticus and sudden, unexpected death in epilepsy. Although these facts should promote the wider use of differential dosing in selected cases, a credible hypothesis is needed that defines the differential dosing strategy and application in cyclic epilepsy and for the greater purpose of preventing harmful outcomes.